Chemocatalytic Conversion of Cellulose into Key Platform Chemicals - Guangbi Li; Wei Liu; Chenliang Ye; Xiaoyun Li; Chuan-Ling Si (International Journal of Polymer Science)
Chemocatalytic transformation of lignocellulosic biomass to value-added chemicals has attracted global interest in order to build up sustainable societies. Cellulose, the first most abundant constituent of lignocellulosic biomass, has received extensive attention for its comprehensive utilization of resource, such as its catalytic conversion into high value-added chemicals and fuels (e.g., HMF, DMF, and isosorbide). However, the low reactivity of cellulose has prevented its use in chemical industry due to stable chemical structure and poor solubility in common solvents over the cellulose. Recently, homogeneous or heterogeneous catalysis for the conversion of cellulose has been expected to overcome this issue, because various types of pretreatment and homogeneous or heterogeneous catalysts can be designed and applied in a wide range of reaction conditions. In this review, we show the present situation and perspective of homogeneous or heterogeneous catalysis for the direct conversion of cellulose into useful platform chemicals.